Internet Addiction among Nursing Students in Kathmandu - Sapkota, Asha (Journal of Nursing Education of Nepal, 2023)
Introduction: Life has become easier with the advent of internet; however excessive use of internet  has created a lot of problems. Use of Internet for education, recreation and communication is increasing  day by day. The nursing students use internet for their academic purposes. The availability of internet  on the mobiles and the computer/laptops makes the student to access the internet very easily, thus there  is a chance of internet addiction. The aim of the study was to find out the internet addiction among  nursing students. Methods: A descriptive cross-sectional research design with non probability purposive sampling  technique was used. A total of 113 BSc nursing students studying at Maharajgunj Nursing Campus  (MNC) of the Institute of Medicine during September and October 2018 were included. Self administered structured questionnaire was used for data collection. Descriptive and inferential statistics  was used for data analysis.  Results: Study findings revealed that the age of the respondents ranged from 18-26 years with mean age  ± SD=20.84±1.57. Almost all (90.3%) were living in the hostel and almost all (97.3%) of respondents  utilized internet for educational and non-educational purposes. Most (92.9%) of the respondents were  average on-line user (mild addiction). Of the total, 6.2% were experiencing occasional or frequent  problems (moderate addiction) while 0.9% was significant problems (severe addiction). There was  significant association of internet addiction level with educational level (p=0.005), mother’s education  (p=0.002) and occupation (p=0.044). Conclusion: Nursing students are utilizing the internet for educational and non educational activities  which causes internet addiction. Counseling and education should be emphasized to increase awareness  to prevent internet addiction among the nursing students.
Keywords: Academic; Internet Addiction; Nursing Students